Making Fewer Strangers: Networking Networks (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
One of our PLAIO goals is to create and nourish an international community of those interested in the assessment of prior learning in all of its many forms. Beginning here, and to be included in all future issues of our journal, we gather “networks” that exist and to which we can turn for information and connections with others in this field. If you have a PLA-related network that should be added to our list-in-process, please let us know. Thanks to many colleagues who provided the following information and to Andrina Wafer for her invaluable insights on many of these networks.